KORELASI KETERAMPILAN MENYIMAK APRESIATIF TEKS CERPEN DENGAN KETERAMPILAN MENULIS TEKS CERPEN SISWA KELAS XII SMA NEGERI 2 PARIAMAN - Sugihartati, Agnes; Asri, Yasnur; Gani, Erizal (Universitas Negeri Padang, 2019)
ABSTRACT The purpose of this research there are three. First, describe the skills listening appreciative poem grade XII SMA Negeri 2 Pariaman. Second, it describes the text short story writing skills of students of class XII SMA Negeri 2 Pariaman, and third, describing the correlation of the short story with appreciative listening skills writing skills text short grade XII SMA Negeri 2 Pariaman. Theory related to this research is the theory of (a) the skill of writing short stories, (b) the text of the short story, and (c) skills listening appreciative short story.This research type is quantitative descriptive method. The design used in this research is the design korelasional. The population of this research is to grade XII SMA Negeri 2 Pariaman are registered on the 2018/2019 academic year, i.e. 268 students. The sample in this research are determined by proportional random sampling of 15% of the population, i.e. 40 students. Research data is a score test results and appreciative listening skills short score test results text short story writing skills. results of the research there are three. First, the skill to listen appreciative short grade XII SMA Negeri 2 Pariaman is located on more than enough qualifications (LdC) with an average value of 75.21. Secondly, the text of the short story writing skills of students of class XII SMA Negeri 2 Pariaman is located on more than enough qualifications (LdC) with an average of 75.00. Kata Kunci: Korelasi, Menyimak Apresiatif Teks Cerpen, Keterampilan Menulis Teks Cerpen